Ethnic Chinese in Indonesia - Winarta, Frans Hendra (Pelita Harapan University, 2002)
In May 1998 riots, it was reported that 1200 people killed and more than 160 women gangraped. The victims are ethnic Chinese. The May 1998 riots are inhuman. The protection of a citizens life is a right of every citizen guaranteed under the Indonesian Constitution. Article 281 paragraph 2 of 1945 constitution states that